Perceived maternal parenting self-efficacy scale: Factor structure and psychometric properties among Portuguese postpartum women - Monteiro, Fabiana (2022)
The aim of this study was to investigate the factor structure and psychometric properties of the Perceived Maternal Parenting Self-Efficacy (PMPS-E) Scale among Portuguese postpartum women. Data were collected through an online survey placed on social media websites targeting Portuguese adult women in the postpartum period (0–12 months after delivery). The total sample consisted of 893 participants who gave birth after 37 weeks of gestation. After conducting exploratory and confirmatory factor analyses, our results revealed that a correlated three-factor model yielded a significantly better fit to the data than the original four-factor model. High reliability was found for the total scale (α= 0.95) and for the three factors (α from 0.88 to 0.94). The PMPS-E presented significant and moderate to large correlations with other measures related to maternal self-efficacy. Participants who were multiparous, had older infants (>5 months old) and perceived their infant temperament as easy reported higher maternal parenting self-efficacy than those who were primiparous, had younger infants (≤5 months old) and perceived their infant temperament as difficult. The results of this study showed that the European Portuguese version of the PMPS-E is a valid and reliable instrument for assessing maternal parenting self-efficacy among postpartum women. Implications for practice: The PMPS-E may be a valuable instrument to detect parenting self-efficacy difficulties among postpartum women and thus contribute to strategies to improve women’s overall psychological adjustment to the postpartum period, with a possible impact on the mother-infant relationship.